Ultrasound-Guided Costoclavicular Brachial Plexus Block: Sonoanatomy, Technique, and Block Dynamics. Issue 2 (March 2017) - Li, Jia Wei; Songthamwat, Banchobporn; Samy, Winnie; Sala-Blanch, Xavier; Karmakar, Manoj Kumar
Abstract : Background and Objectives: This study aimed to describe in detail the relevant sonoanatomy, technique, and block dynamics of an ultrasound-guided costoclavicular brachial plexus block (BPB). Methods: Thirty patients scheduled for hand or forearm surgery under a BPB underwent transverse ultrasound imaging of the medial infraclavicular fossa to identify the cords of the brachial plexus at the costoclavicular space (CCS). An ultrasound-guided BPB was then performed at the CCS with 20 mL of 0.5% ropivacaine. Sensory-motor blockade of the ipsilateral median, radial, ulnar, and musculocutaneous nerves were assessed at regular intervals for 30 minutes after the injection. Successful block was defined as being able to complete surgery under the BPB. Results: The CCS was visualized as a well-defined intermuscular space lying deep and posterior to the mid-point of the clavicle. The cords of the brachial plexus were clustered together lateral to the axillary artery within the CCS. The costoclavicular BPB was successfully performed in all patients, and the median onset time for sensory and motor blockade of all the 4 nerves was 5 [5–15] and 5 [5–10] minutes, respectively. Complete sensory blockade of all the 4 nerves was achieved in 30 [20–30] minutes, and the BPB was successful in 29 (97%) of 30 patients. There were no complications directly related to the technique or the local anesthetic injection. Conclusions: This report describes a novel technique of infraclavicular BPB at the costoclavicular space that produces rapid onset of BPB. Future research should compare the safety and efficacy of this new technique with the traditional lateral sagittal infraclavicular BPB.